Anticancer Activity of Synthesized ZnO and ZnO/AgCl Nanocomposites against Five Human Cancer Cells - Fattima Al-Zahra Gabar Gassim; Ali Jabbar Jasim Makkawi (Universitas Gadjah Mada, 2023)
In this work, a refluxing method is used to prepare nanoparticles of zinc oxide (ZnO NPS) and zinc oxide /silver chloride nanocomposites (ZnO/AgCl NCS). The structural properties of nanocrystals are studied by Atomic Force Microscope (AFM), X-Ray Diffraction (XRD), and Field Emission Scanning Electron Microscopy (FE-SEM) to determine the average crystal size, morphology, particle size and average grain size of nanocrystals. The results of anticancer efficiency of ZnO NPs and ZnO/AgCl NCs show cytotoxic activity against five human cancer cells, namely hepatocellular carcinoma, rhabdomyosarcoma (RD), colorectal carcinoma (HCT116), mammary gland (MCF-7), and epidermoid carcinoma (Hep2) compared against doxorubicin. The anticancer mechanism of pure and nanocomposites ZnO are suggested according to the release of Zn+2 and the production of reactive oxidation species (ROS) and the effect of these species on cancer inhibition.